2011
DOI: 10.1016/j.chemphyslip.2011.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Functional lipidomics of oxidized products from polyunsaturated fatty acids

Abstract: Because of their high degree of unsaturation, polyunsaturated fatty acids (PUFA) in mammals, with mainly 18, 20 and 22 carbons, can easily be autooxidized, and converted into many oxidized derivatives and degradation products. This short review reports on some of those relevant to the evaluation of oxidative stress in situ. In addition, the enzyme-dependent oxygenation by both dioxygenases and monooxygenases is briefly reviewed by functional and/or metabolic categories, pointing out the structure variety and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…44-46 HHE on the other hand is derived from the oxidation of n-3 PUFAs (α-linolenic acid, eicosapentanoic acid and docosahexanoic acid) and it is generated in humans and rodents at higher concentration than HNE. 47-49 In the present study, we found carnosine-HHE conjugates in WT and ApoE-null mice on a normal chow after a single dose of ODC; however, carnosine-HNE was detected only in mice receiving a high-fat diet suggesting that HHE is the major aldehyde formed during low levels of lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…44-46 HHE on the other hand is derived from the oxidation of n-3 PUFAs (α-linolenic acid, eicosapentanoic acid and docosahexanoic acid) and it is generated in humans and rodents at higher concentration than HNE. 47-49 In the present study, we found carnosine-HHE conjugates in WT and ApoE-null mice on a normal chow after a single dose of ODC; however, carnosine-HNE was detected only in mice receiving a high-fat diet suggesting that HHE is the major aldehyde formed during low levels of lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Modification of these FA species through enzymatic or non-enzymatic processes yields a huge number of modified FA species. A good example is the family of eicosanoids which are produced from the oxidation of twenty-carbon, n-3 or n-6 polyunsaturated fatty acids 5, 6 .…”
mentioning
confidence: 99%
“…For example, the composition of phospholipids (PLs) with varying acyl chain length and the number of unsaturated C=C double bonds define the characteristics and functional efficacy of neural membranes (Van Meer et al 2008). Apart from their structural role, polyunsaturated lipids are further precursors for important second messengers such as arachidonic (C20:4), eicosapentaenoic (C20:5), docosapentaenoic (C22:5) and docosahexaenoic (C22:6) acids (Guichardant et al 2011) which are partly known to be involved in neuronal signaling (Gantz and Bean 2017). This is in agreement with the recently proposed hypothesis of “small molecule co-transmission” (Nusbaum et al 2017), which suggests that membrane compounds regulate neurotransmitter signaling independently and in conjunction transmitter receptors.…”
Section: Discussionmentioning
confidence: 99%